1978
DOI: 10.1093/nar/5.12.4837
|View full text |Cite
|
Sign up to set email alerts
|

Participation of X47-fluorescamine modified E. coli tRNAs in in vitro protein biosynthesis

Abstract: The reaction of fluorescamine with primary amino groups of tRNAs was investigated. The reagent was attached under mild conditions to the 3'-end of tRNAPhe-C-C-A(3'NH) from yeast and to the minor nucleoside x in E. coli tRNAArg, tRNALys, tRNAMet, tRNAIle and tRNAPhe. The primary aliphatic amino groups of these tRNAs react specifically so that the fluorescamine dye is not attached to the amino groups of the nucleobases. E. coli tRNA species modified on the minor nucleoside X47 can all be aminoacylated. An involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…GTP could be visualized by STEM imaging and mass measurement (Blechschmidt et al, 1993). Sprinzl and Faulhammer (1978) demonstrated that the fluorescence of the fluorescamine-modified Phe-tRNAP'" is not affected upon ternary complex formation with EF-Tu .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…GTP could be visualized by STEM imaging and mass measurement (Blechschmidt et al, 1993). Sprinzl and Faulhammer (1978) demonstrated that the fluorescence of the fluorescamine-modified Phe-tRNAP'" is not affected upon ternary complex formation with EF-Tu .…”
Section: Discussionmentioning
confidence: 98%
“…This low modification rate could not be explained by sterical hindrance of the gold cluster because the modification with NEM gives the same yield. Sprinzl and Faulhammer (1978) describe a modification of 72% of the tRNAPhe with fluorescamine at acp3U. Asuming that all molecules containing the acp3U base can react with fluorescamine, this would indicate a partial undermodification of tRNAPhc in respect to acp3U47.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when its base )<47 is labeled with fluorescamine, no change in fluorescence is observed upon ternary complex formation [62], suggesting that the variable region although possibly 'covered' to some extent by EF-Tu, is probably not in very close contact with the factor. In any event, the variable region is not believed to be essential for ternary complex formation.…”
Section: The Variable Loopmentioning
confidence: 99%